The golden age of the world economy and Portuguese economic growth: applied study, 1950-2018 - Ricardo Ferraz (Cogent Economics & Finance, 2022)
During the Golden Age (1950-1973), Portugal stood out in the international scene, converging economically with the group of more industrialised economies. In this paper, we start by analysing the main factors that explain the extraordinary economic performance of Portugal during that crucial period of its history. Next, we construct and estimate a dynamic model to quantify the relationship between those factors and the Portuguese economic growth in the time horizon that stretches from the Golden Age to present days. The results obtained show that investment and international trade have been contributing positively to economic growth of Portugal in the last decades, 1950-2018. The conclusions of this paper, which are in line with the international literature, reinforce the importance for Portuguese decision-makers to adopt political measures to open the economy and to create favourable conditions for investment in order to obtain a faster economic growth that allows a robust convergence with the most industrialized nations.
Keywords: 330; economic growth; golden age; international trade; investment; Portugal